El sionismo norteamericano. Tres textos de Edward W. Said - Said, Edward (Revista de Estudios Árabes, 2014)
The author describes how the American Zionist organizations have total control of U.S.A. government policies in the Middle East, the American media, and even over the Israeli government. The writer describes the American Jewish community as more extremist than the Israeli Likud party. He notes the misguided notions that American Jews have regarding the Palestinians, as they never bothered to know them. He criticizes Arab countries disunity and their American controlled governments. According to him, Camp David, the Oslo Accords or any other peace plan will fail as long as they are based on American-Israeli political control of any Middle East negotiations.